Effect of Peer-Mentoring Programs on Academic Motivation and School Belonging in First-Generation Learners - Torres, Jennifer; Chen, Daniel; Peixoto, Beatriz (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to examine the effectiveness of a peer-mentoring program on enhancing academic motivation and school belonging in first-generation learners. A randomized controlled trial design was used with 30 first-generation students from Canada, randomly assigned to either an intervention group (n = 15) that participated in an eleven-session peer-mentoring program or a control group (n = 15) that received no intervention. The sessions, conducted weekly over three months, focused on academic goal setting, motivation, school engagement, and emotional support. Data were collected at three time points—pre-test, post-test, and five-month follow-up—using the Academic Motivation Scale and the Psychological Sense of School Membership scale. Repeated measures ANOVA with Bonferroni post-hoc tests were conducted in SPSS-27 to analyze group differences over time. The intervention group showed significant improvements in both academic motivation and school belonging across time compared to the control group. Repeated measures ANOVA revealed a significant interaction effect between time and group for academic motivation (F(2, 56) = 28.42, p < .001, η² = .49) and for school belonging (F(2, 56) = 27.35, p < .001, η² = .47). Bonferroni post-hoc tests confirmed significant increases from pre-test to post-test and pre-test to follow-up for both variables in the intervention group (p < .001), with no significant change between post-test and follow-up, indicating sustained effects. The control group showed no significant changes over time. Peer mentoring significantly improves academic motivation and school belonging among first-generation learners, and these gains are sustained over time. Structured, relational interventions that emphasize shared experience, goal setting, and emotional support can play a key role in fostering educational engagement and persistence in marginalized student populations.